THE INFLUENCE OF DIVIDEND POLICY AND PROFITABILITY WITH FIRM SIZE - Sholikhah, Septiana Mar'atus; Buchori, Buchori; Rinnanik, Rinnanik; Muntama, Muntama (JURNAL ECONOMICA : Research of Economic And Economic Education, 2023)
AbstrakThis study set out to ascertain how dividend policy, profitability, and debt policy affected corporate value. In addition to determining if company size can strengthen the impact of profitability, debt policy, and dividend policy on firm value. The study's research methodology was moderate regression analysis (MRA). Theoretically, this approach is suitable for investigating the influence variable after including a moderating component. The novelty aspect of this analysis is the inclusion of firm size as a moderating variable, which is thought to strengthen or decrease the relationship between dividend policy, profitability, and debt policy and firm value. The findings of this study demonstrate how profitability and dividend policy impact corporate value. Next, the impact of dividend policy on firm value is moderated by the size of the company. However, the impact of profitability on firm value is unaffected by the size of the company.Keywords: Dividend Policy, Debt Policy, Firm Value, Financial Behavior, Profitability